(untitled) (International Journal of Current Engineering and Technology, 2014)
Electromyography (EMG) provides useful information for diagnosis. This paper deals with a computer based expert system which has been developed for the diagnosis of HD using the features of EMG signal recorded from the disease site. In this study frequency domain parameters of the EMG signal and signal under both the healthy and leprosy conditions of the subjects for the disease diagnosis using an artificial neural network.